Soil-borne viruses in major potato growing areas of Pakistan (The Journal of Plant Protection Sciences, 2024)
An extensive field surveys on important soil-borne viruses of potato were conducted in Hazara and Malakand Divi sions during potato growing seasons in 2011-12. Incidence and distribution of Potato mop-top pomovirus (PMTV)  and Tobacco rattle tobra virus (TRV) was reported on the basis of characteristic symptoms expression, bait test,  infectivity assays and double antibody sandwich-enzyme linked immunosorbent assay (DAS-ELISA). Both the  viruses were prevalent in Hazara and Malakand divisions. The average symptoms based incidence in Hazara divi sion for PMTV was 8.83% and TRV was 6.80% while in Malakand division the average symptoms based inci dence for PMTV was 8.46% and TRV was 9.95%. DAS-ELISA based average incidence in Hazara of PMTV and  TRV was 17.34% and 11.99% respectively. The average DAS-ELISA based incidence in Malakand division for  PMTV was 21.36% and TRV was 13.71%. The highest symptom based incidence of PMTV in the Hazara was in  Baffa 10.75% and in Kalam 10.34% was in Malakand division whereas the highest incidence of TRV in Hazara  was in Gojri 8.08% and in Malakand was in Shangla-top 11.62 %. The highest incidence of PMTV based on  ELISA was recorded in samples collected from the farmers field at Baffa (21.73%) of Hazara while (23.80%) in  Kalam of Malakand division. The highest incidence of TRV based on ELISA in Hazara was found in Mangal  14.28% and in Malakand division the highest incidence was in Shangla Top 17.39%. Isolates of PMTV and TRV  were characterized using biological and serological techniques. Biological characterization of the field isolates  revealed that variability in the symptoms produced by them on host plant. The interaction and association of vi ruses (PMTV and TRV) and their vectors was calculated by using Jaccard index of similarity. The association of  PMTV to its vector Spongosporsa subteranea in Hazara division was found 27.0% while their association in  Malakand division was found 24.4%. The TRV associated to its vectors Trichodorus in Hazara division was found  8.94% while in Malakand division was 20.70%. It was concluded that molecular studies will be required to deter mine variability among the prevalent isolates of PMTV and TRV.
Keywords: Soil-borne virus; nematode; fungus; incidence; potato; Pakistan